Relationships Between Reproductive History and Mortality From Cardiovascular Diseases Among Japanese Women: The Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC) Study - Tanigawa, Kanami (J Epidemiol, 2020)
BACKGROUND: Reproductive history has been addressed as a risk factor for cardiovascular disease (CVD). We examined the relationship between reproductive history and CVD mortality in Japanese women. METHODS: We followed 53,836 women without previous CVD or cancer history from 1988–1990 to 2009 in a prospective cohort study. Hazard ratios (HRs) and 95% confidence intervals (CIs) of CVD mortality were estimated according to the number of deliveries and maternal age at first delivery. RESULTS: During the follow-up, 2,982 CVD-related deaths were identified. There was U-shaped association between the number of deliveries and risk of CVD mortality with reference to three deliveries, although the excess risk of CVD mortality associated with ≥5 deliveries was of borderline statistical significance. The corresponding multivariable HRs were 1.33 (95% CI, 1.12–1.58) and 1.11 (95% CI, 0.99–1.24). In addition, higher CVD mortality was associated with maternal age ≥28 years at first delivery than maternal age of 24–27 years at first delivery. The multivariable HRs were 1.22 (95% CI, 1.10–1.36) for 28–31 years at first delivery and 1.26 (95% CI, 1.04–1.52) for ≥32 years at first delivery. Moreover, among women with ≥3 deliveries, maternal age ≥28 years at first delivery was associated with 1.2- to 1.5-fold increased CVD mortality. CONCLUSION: The number of deliveries showed a U-shaped association with risk of CVD mortality. Higher maternal age at first delivery was associated with an increased risk of CVD mortality, and excessive risk in women aged ≥28 years at first delivery was noted in those with ≥3 deliveries.